Outbreak of Rice Blast Disease at Yeoju of Korea in 2020 - Chung, Hyunjung; Jeong, Da Gyeong; Lee, Ji-Hyun; Kang, In Jeong; Shim, Hyeong-Kwon; An, Chi Jung; Kim, Joo Yeon; Yang, Jung-Wook (The Plant Pathology Journal, 2022)
Rice blast is the most destructive disease threatening stable rice production in rice-growing areas. Cultivation of disease-resistant rice cultivars is the most effective way to control rice blast disease. However, the rice blast resistance is easy to breakdown within years by blast fungus that continually changes to adapt to new cultivars. Therefore, it is important to continuously monitor the incidence of rice blast disease and race differentiation of rice blast fungus in fields. In 2020, a severe rice blast disease occurred nationwide in Korea. We evaluated the incidence of rice blast disease in Yeoju and compared the weather conditions at the periods of rice blast disease in 2019 and 2020. We investigated the races and avirulence genes of rice blast isolates in Yeoju to identify race diversity and genetic characteristics of the isolates. This study will provide empirical support for rice blast control and the breeding of blast-resistant rice cultivars.